Analisis Penanganan Kargo Miscellanous Dangerous Goods pada PT. Angkasa Pura Kargo Cabang Pontianak - Dedek Fitri Yanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Kargo delivery is a common activity that involves the transfer of goods from the place of origin to the destination. In this shipment, there are several types of kargo, one of which is the Dangerous Goods kargo. This study aims to find out how to handle and what are the obstacles in the process of handling Miscellanous Dangerous Goods kargo. The research method used in this research is a qualitative research type. Qualitative research is often called naturalistic research because the research is carried out in natural conditions (natural setting) which is also known as ethnographic methods. Data collection techniques using interviews, observation, documentation and research at PT. Angkasa Pura Kargo Pontianak Branch. The results showed that there were handling efforts made by PT. Angkasa Pura Kargo in handling Miscellanous Dangerous Goods kargo includes administrative handling related to kargo acceptance activities and document inspection such as the completeness of Air Waybill, Shipper Declaration, Dangerous Goods Checklist, then handling in the form of packaging, storage in the warehouse, to loading onto aircraft. Therefore, any handling involving Dangerous Goods kargo must be carefully considered in every detail to minimize the possibility of accidents occurring. Suggestions for PT. Angkasa Pura Kargo Pontianak Branch continues to improve services and supervision, especially during the process of checking goods/kargo for flight safety and security.